Effect of dibenzyl disulphide on partial discharge characteristics in mineral oil–impregnated cellulose pressboard - Mohd Selva, Amran; Azis, Norhafiz; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita; Zainuddin, Hidayat; Mohd Yousof, Mohd Fairouz (Elsevier Ltd, 2026)
This study investigates the partial discharge (PD) characteristics of mineral oil-impregnated cellulose pressboard induced by dibenzyl disulphide (DBDS). Mineral oils with DBDS concentrations of 0 ppm, 1,000 ppm, 5,000 ppm, and 10,000 ppm were thermally aged at 150 °C for 5 days. PD measurements, which included apparent charge, PD repetition rate, and partial discharge inception voltage (PDIV), were performed using needle–plane and plane–plane electrode configurations at 10 mm and 20 mm gap distances. Phase–resolved partial discharge (PRPD) patterns were analysed to assess discharge intensity and phase distribution. Results show that under the needle–plane configuration, PDIV increases by up to 44.3% in pressboards aged with 5000 ppm DBDS at both gap distances. In contrast, under the plane–plane configuration, PDIV of pressboards aged in 1,000 ppm DBDS at both gap distances decreases by up to 56%. PRPD analysis reveals a transition from compact, peak-centred discharges (Type 3) to broad and scattered patterns (Type 6) that indicates progressive surface degradation driven by DBDS contamination.